Dissimilar friction stir welding between polycarbonate and AA 7075 aluminum alloy - Moshwan, R.; Rahmat, S.M.; Yusof, F.; Hassan, M.A.; Hamdi, M.; Fadzil, M. (2015)
In this paper, the effects of process parameters, such as the tool rotational and traverse speeds, on temperature evolution and the microstructural and mechanical properties of dissimilar friction stir welding between 3 mm thick AA 7075 aluminum alloy and polycarbonate (PC) plates were investigated. The tool rotational and traverse speeds were varied from 3 000 to 3 500 rpm and 50 to 150 mm min(-1), respectively. The joint fabricated at 3 250 rpm and 100 mm min(-1) yielded a highest tensile load of 586 N. Microstructural analysis of the stir zone revealed an interlock phenomenon, the transportation of AA 7075 in polycarbonate, and the absence of ceramic-type (carbide, hydride or oxide) compounds. Microhardness (HV) measurement on the weld zone showed an uneven distribution due to the complicated microstructure of the welded joint. The maximum temperatures of 164 degrees C and 66 degrees C were obtained at 3 250 rpm and 100 mm min(-1) at a distance of 5 mm away from the welding centerline in the AA 7075 and PC side, respectively.